La Aufklärung, desacuerdo y lo político en Jacques Rancière y Michel Foucault. - Fallas-Vargas, Fabrizio (Revista Letral, 2016)
This paper explores the main tasks of critical research, which according to a negative dialectial reading of Rancière/Foucault link, targets the actuality of Kant’s question and the question of philosophy. What is Critique? Why Philosophy? What is Thinking today? This in order to deploy the central conflicts and affinities between the two philosophers, articulated within this rigorous and unruly reflective experience that we call philosophy and it s privileged field in the case of both theoretical and conceptual universes, namely: the object of politics.
Artículo científico
Keywords: Política; Crítica; Expresión; Filosofía; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects